The high impact of using animation in enhancing education in schools - Badi, Hana J.; Zeki, Akram M. (IIUM Press, 2011)
Educating children by using the right and appropriate way is one of the most important things that we should take care of. Traditional way of teaching is no longer useful or enough to deliver information to the students nowadays. That happens due to the new technologies that rise in our life each day. Enhancing education by using new technologies is one solution to provide better understanding for students and more comfort for teachers.